THE LEADERSHIP ROLE OF THE KYAI IN THE ORGANIZATION OF THE BOARDING SCHOOL AT THE DARUL FALAH BOARDING SCHOOL PARE KEDIRI - Fikri, Ahmad (Jurnal Inovatif Manajemen Pendidikan Islam, 2023)
The idea The figure of the kiai is a central figure in Islamic boarding schools where the kyai has its own characteristics of leadership compared to other educational figures. In developing Islamic boarding schools, of course, the kiai have roles and strategies that are adapted to the conditions of the boarding schools being managed, such as development, strategies for increasing human resources, strategies for selecting organizational members and so on. The main role of the kyai in an Islamic boarding school is to direct and guide his students so that they become pious people with good morals who are useful for the nation, state and religion. In practice, the kyai assigns a special organization whose job is to take care of all matters relating to the santri.